Resultative Constructions in Albanian and English - Kurani, Aida (Richtmann Publishing, 2011)
This paper discusses the expression of resultative meaning in Albanian and English. This two languages bear bothresemblance and dissimilarity when it comes to building resultative constructions.1 We argue that secondary predicates with resultativemeaning, widespread in English and other Germanic languages, don’t occur as often in Albanian. Instead, Albanian uses mostly otherstrategies, like resultative clauses, verb + ablative construction, gerund phrases, etc. This fact should be taken into consideration duringthe translation from English into Albanian and vice versa.